鍼灸施術が唾液と尿に及ぼす影響 : 唾液アミラーゼ活性および酸化還元電位と水素イオン濃度を指標として - 渡邉, 勝之; 篠原, 昭二 (人体科学, 2009)
We previously clarified that acupuncture and moxibustion applied to strongly reactive points had increased AI (Aging Index) and affected the pH of the local epidermis. In this study, we evaluated the influences of acupuncture and moxibustion on the ORP (Oxidation-Reduction Potential), AI and pH of saliva and urine. In treatment group, the pH of saliva decreased. While the ORP of urine showed decrease, its pH showed increase after treatment. In dietary group, the ORP of saliva decreased but its pH showed increase. The ORP of urine increased but its pH showed decrease. In the study of the α-amylase activity, treatment group showed significant decrease, whereas dietary group showed significant increase. Our data demonstrate that the AI and pH of both saliva and urine showed opposite changes between treatment and dietary group. Similarly, salivary α-amylase activity showed opposite changes between two groups.